Análisis del artículo 207-2 del estatuto tributario nacional el cual creó nuevas rentas exentas y su incidencia en las finanzas del estado (2010)
The restlessness to know if the State is fulfilling the objectives in its finances, granting tributary benefits to different sectors from the economy, such as the hotel sector, the primary sector agricultural, the power sector, among others, to generated restlessness to analyze article 207-2 of National Statute Tributary, which I create new rents free from year 2002 with the expedition of 2002 law 788. The objective is to determine if these exemptions in the tax on the rent and complementary, compensate within the General Budget of the Nation, the income that stop perceiving the State when granting these tributary benefits